Correlation of nanoscale behaviour of forces and macroscale surface wettability. Issue 34 (11th August 2016) - Rana, Abhimanyu; Patra, Abhijeet; Annamalai, Meenakshi; Srivastava, Amar; Ghosh, Siddhartha; Stoerzinger, Kelsey; Lee, Yueh-Lin; Prakash, Saurav; Jueyuan, Reuben Yeo; Goohpattader, Partho S.; Satyanarayana, Nalam; Gopinadhan, Kalon; et al.
Abstract : We demonstrate a method based on atomic force microscopy which enables local probing of surface wettability. Abstract : In this manuscript, we demonstrate a method based on atomic force microscopy which enables local probing of surface wettability. The maximum pull-off force, obtained from force spectroscopy shows a remarkable correlation with the macroscopically observed water contact angle, measured over a wide variety of surfaces starting from hydrophilic, all the way through to hydrophobic ones. This relationship, consequently, facilitates the establishment of a universal behaviour. The adhesion forces scale with the polar component of surface energy. However, no such relation could be established with the dispersive component. Hence, we postulate that the force(s) which enable us to correlate the force spectroscopy data measured on the nanoscale to the macroscopic contact angle are primarily arising from electrostatic-dipole–dipole interactions at the solid–liquid interface. London forces play less of a role. This effect in is line with density functional theory (DFT) calculations suggesting a higher degree of hydroxylation of hydrophilic surfaces. This result shows that molecular simulations and measurements on an atomic scale can be extrapolated to macroscopic surface wetting problems.